Does a universal test and treat strategy impact ART adherence in rural South Africa? ANRS 12249 TasP cluster-randomized trial - (:unkn) unknown (My University, 2015)
Background: HIV treatment guidelines are recommending ART at increasingly higher CD4 counts for maximizing individual and population benefits. However, the expansion of ART use may be at the expense of optimal adherence. We report on adherence and virological suppression when initiating ART at different CD4 thresholds within the Treatment as Prevention (ANRS 12249) trial of universal home-based testing and immediate ART initiation in rural KwaZulu-Natal.Methods: Using data of a cluster-randomised trial of immediate ART vs. initiation according to current national guidelines (CD4≤350cells/mm3), we compared adherence levels (≥95% vs. < 95%) measured using a visual analogue scale (VAS) and pill count (PC) and virological suppression at 6 months(< 400 c/mL) according to CD4 count at ART initiation through logistic regression models, adjusting for possible confounders (age, sex, marital status, education and employment).Results: During March 2012-May 2014, 601 participants who were not on ART entered care in trial clinics; 382 initiated ART; 254 have completed ≥6 months on ART, 227 of whom had 6 months HIV RNA data and were included in analyses. 169 were women; median (IQR) age and CD4 at ART initiation were 35 years (28, 46) and 313cells/mm3 (206, 513). Adherence ≥95% at 6 months was high (88% and 83% by PC and VAS, respectively) with no evidence that this was associated with CD4 at initiation (aOR=0.97 per 100 cells/mm3 higher, 95%-CI: 0.83-1.12, p=0.65 for VAS; aOR 1.13 per 100cells/mm3 higher, 0.98-1.31, p=0.09 for PC). Male sex was independently associated with < 95% adherence (2.58, 1.24-5.35, p= 0.01; ref. females). 83% (183/227) of those who started ART achieved HIV suppression by 6 months with no association with CD4 at initiation (1.13 per 100cells/mm3 higher, 0.96-1.33, p=0.40). Compared to those with ≥95% adherence by VAS, individuals with < 95% adherence were somewhat less likely to suppress (0.44, 0.19-1.0
Keywords: African Research